Development of a real-time performance measurement and feedback system for alpine skiers - Kirby, R. (Sports Technology, 2009)
Timely and accurate feedback on athlete performance is a key contributing factor to improving that athletic performance. For alpine skiers, feedback usually comes in the form of video, coach's comments, and the timing system. Video and coach's comments come well after the performance (usually many hours) and are subjective. The timing systems give only one or a few data points which represent as many as 50 gates, making it too general as a training tool. The aim of the present article is to describe the development of a real-time performance measurement and feedback system for training alpine skiers using Optical Navigation Technology and to present the results of field work done with alpine ski racers. In order to understand the special needs of alpine skiers, the first section of this article describes what racers and recreational skiers consider to be the ideal turn. One of the key characteristics of this ideal turn is the lack of lateral displacement. This article explores a new method for precisely measuring lateral displacement, converting that measured displacement into audible feedback which is in turn fed back to the skier in real-time. Lastly, the results of a field study are presented in which the perceived benefits of real-time feedback were demonstrated with 100% of the subjects stating that real-time feedback had definitely or probably helped them better understand their carving skills and 83% of subjects stating that the real-time feedback definitely or probably helped them improve their carving skills after only one two-hour session.